Proceedings of the 7th International Conference on English Language and Teaching (ICOELT 2019) 2020
DOI: 10.2991/assehr.k.200306.045
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Writing Strategy for Teaching Writing Descriptive Text

Abstract: Writing is a complex process that allows students to explore thoughts and ideas and make them visible and concrete. Teaching writing is a process of giving skills to students on how to communicate and express their thought, feelings, and opinions in a written language. Writing skill is a skill rarely taught to learners either at SMP or SMA level since it is considered difficult, not tested in semester or final examination, teacher is more often preoccupied with explaining the parts (generic structure) of a tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…A meta-analysis by Graham and Perin ( 2007 a) demonstrated that collaborative writing can have a positive and substantial impact on the quality of secondary students’ writing (effect size = 0.75). This was illustrated in a study by Harlena and colleagues ( 2019 ), which found that collaborative writing improved not only secondary school students’ writing, but also increased their involvement and their enthusiasm during the writing process.…”
Section: Collaborative Writingmentioning
confidence: 91%
See 2 more Smart Citations
“…A meta-analysis by Graham and Perin ( 2007 a) demonstrated that collaborative writing can have a positive and substantial impact on the quality of secondary students’ writing (effect size = 0.75). This was illustrated in a study by Harlena and colleagues ( 2019 ), which found that collaborative writing improved not only secondary school students’ writing, but also increased their involvement and their enthusiasm during the writing process.…”
Section: Collaborative Writingmentioning
confidence: 91%
“…However, this point of view was challenged by the WWC model (Graham, 2018b ; Storch, 2019 ). Multiple studies have pointed out the usefulness of collaborative writing in the classroom (Bouwer et al, 2022 ; Graham & Perin, 2007 ; Harlena et al, 2019 ). Unfortunately, it remains unclear whether students benefit most from collaborating throughout the complete writing process or from alternating between collaborative and individual writing phases.…”
Section: Impact Of Explicit Instruction and Collaborative Writing On ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Writing is a complex process that allows students to explore ideas and make them visible and concrete (Harlena, 2020). Developing students’ writing competencies can not only improve students’ language literacy but also help enhance their learning abilities, including the ability to reflect, select, evaluate, critically, and transcript (Yeung et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both Ferrari and Basa (2017) and Ubilla, Gómez and Sáenz (2017) highlight the importance of collaborative writing; the authors concluded that technology is a good support to work collaboratively on text production. In addition, Harlena (2020), Hatika (2017) and Chandra (2015) mention that collaborative writing can be used as a strategy to teach. Harlena in his research obtained a mean of 76.23 in the GE and from the CG 66.88; Hatika achieved a mean of 73.30 in the posttest and 59, 32 in the pretest of his experimental group; and Chandra obtained a mean of 78.05 for the GE and 50.25 for the CG.…”
Section: Literature Reviewmentioning
confidence: 99%